(untitled) (Asian Journal of Medical and Biological Research, 2016)
The present work was conducted to evaluate the variability in linear body measurements; to investigate the relationship between body linear measurements and live weight and to predict live weight of F1 Brahman crossbred cattle using body measurements. A total of 123 male and 87 female F1 Brahman crossbred cattle of 6-36 months age and weighing from 63 to 535 kg were used for the study over a period from 2010 to 2014. The study revealed that that most of the morphological measurements were linearly increased with the advances of age. The body weight had highest correlation coefficient with the heart girth around the chest (r=0.96, p<0.001) and lowest with canon bone length (r=0.49, p<0.001) compared with other body measurements. The correlations of body weight with tail length, ear length, canon bone length and canon bone width were at medium level (r=0.51-0.79). Grouping of data according to age indicated that heart girth in >24 months group had highest correlation coefficient (r=0.96) with body weight compared to ?12 months (r=0.92) and >12-24 months (r=0.95) group. The stepwise regression models revealed that heart girth singly accounted highest variation (93%) in body weight for all animals. Thus, the general equation for prediction of live weight of Brahman crossbred cattle was Y=4.07HG356 (±6.96) where Y=live weight (Kg), HG=heart girth around the chest (cm). The regression equations for the live weight were Y=2.71HG191 (±13.5), Y=4.05HG357 (±9.77) and Y=4.87HG471 (±23.0) for ?12, >12-24 and >24 months age groups. The best model for estimating body weight was obtained using HG and body length (BL) for all animals Y=2.83HG+1.80BL392 (±6.69). These results suggested that prediction equations based on HG or in combination of HG and BL can be used efficiently in Brahman crossbred cattle to predict live weight. Asian J. Med. Biol. Res. December 2015, 1(3): 569-577